Alternative meat industry - Elias, Jaan; Springer, Nikki; Wyk, Leon Van; Thomas, Jacob, active 2021; Rouwenhorst, K. Geert (London : Yale School of Management, 2021)
In 2009, when experienced entrepreneur Ethan Brown decided to build a better veggie burger, he set his sights on an exceptional goal - create a plant-based McDonald's equally beloved by the American appetite. To do this, he knew he needed to transform the idea of plant-based meat alternatives from the sleepy few veggie burger options in the grocer's freezer case into a fundamentally different product.
Originally Published InElias, J., Springer, N., Wyk, L.V., Thoma, J., & Rouwenhorst, K.G. (2021). Alternative Meat Industry. 20-033. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Entrepreneurship -- Case studies; Meat substitutes -- Marketing -- Case studies